2020
DOI: 10.1159/000511304
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Shifts in Brain Size and Brain Organization of the Atlantic Sharpnose Shark, <b><i>Rhizoprionodon terraenovae</i></b>

Abstract: Throughout an animal’s life, species may occupy different environments and exhibit distinct life stages, known as ontogenetic shifts. The life histories of most sharks (class: Chondrichthyes) are characterized by these ontogenetic shifts, which can be defined by changes in habitat and diet as well as behavioral changes at the onset of sexual maturity. In addition, fishes experience indeterminate growth, whereby the brain and body grow throughout the organism’s life. Despite a presupposed lifelong neurogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…Since fishes (like other ectothermic vertebrates) grow indeterminately, their brains may exhibit lifelong neurogenesis and brain growth to match the neural demands of the body (Leonard et al ., 1978; Ngwenya et al ., 2013; Zupanc, 2006). For example, our estimate of the brain mass allometric slope was similar to those reported in various other intraspecific studies of fishes, which reported slopes of 0.48–0.57 (Bauchot et al ., 1976) and 0.5 (95% CI 0.46–0.54; Gonda et al ., 2011) for bony fishes and 0.427 (95% CI 0.374–0.480; Lisney et al ., 2017) and 0.46 (95% CI 0.43–0.49; Laforest et al ., 2020) for cartilaginous fishes. Our slope estimate was also similar to evolutionary allometric slopes across cartilaginous fishes broadly (slope = 0.43; Yopak et al ., 2019) and Carcharhiniformes specifically, where brain mass changes with body mass with a slope of 0.52 (Myagkov, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since fishes (like other ectothermic vertebrates) grow indeterminately, their brains may exhibit lifelong neurogenesis and brain growth to match the neural demands of the body (Leonard et al ., 1978; Ngwenya et al ., 2013; Zupanc, 2006). For example, our estimate of the brain mass allometric slope was similar to those reported in various other intraspecific studies of fishes, which reported slopes of 0.48–0.57 (Bauchot et al ., 1976) and 0.5 (95% CI 0.46–0.54; Gonda et al ., 2011) for bony fishes and 0.427 (95% CI 0.374–0.480; Lisney et al ., 2017) and 0.46 (95% CI 0.43–0.49; Laforest et al ., 2020) for cartilaginous fishes. Our slope estimate was also similar to evolutionary allometric slopes across cartilaginous fishes broadly (slope = 0.43; Yopak et al ., 2019) and Carcharhiniformes specifically, where brain mass changes with body mass with a slope of 0.52 (Myagkov, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Using gill surface area as a proxy for oxygen consumption and energetic demand on evolutionary time scales, we found that C. limbatus individuals with a large gill surface area for their body mass may be able to support a higher energetic turnover and, in turn, a larger brain for their body mass. However, brain size is highly variable at large body sizes in cartilaginous fishes (Laforest et al ., 2020). Thus, although our results suggest that individuals with a large brain for a given body mass may also have a large gill surface area, more data is needed spanning the full range of body sizes in C. limbatus .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations